2002
DOI: 10.1038/sj.mp.4000965
|View full text |Cite
|
Sign up to set email alerts
|

Epi-inositol regulates expression of the yeast INO1 gene encoding inositol-1-P synthase

Abstract: Myo-inositol exerts behavioral effects in animal models of psychiatric disorders and is effective in clinical trials in psychiatric patients. Interestingly, epi-inositol exerts behavioral effects similar to myo-inositol, even though epi-inositol is not a substrate for synthesis of phosphatidylinositol. We postulated that the behavioral effects of epi-inositol may be due to its effects on gene expression. Yeast INO1 expression was measured in northern blots. INM1 was determined by ␤-galactosidase activity in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…However, several other reports, using similar cell types, found no effect of myo-inositol on lithium-induced changes in growth cone area (Lucas and Salinas, 1997;Lucas et al, 1998;Hall et al, 2000). The reasons for these differences are not clear, but it should be noted that exogenous inositol can have indirect effects not obviously related to depletion of myo-inositol (Hedgepeth et al, 1997;Shaldubina et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…However, several other reports, using similar cell types, found no effect of myo-inositol on lithium-induced changes in growth cone area (Lucas and Salinas, 1997;Lucas et al, 1998;Hall et al, 2000). The reasons for these differences are not clear, but it should be noted that exogenous inositol can have indirect effects not obviously related to depletion of myo-inositol (Hedgepeth et al, 1997;Shaldubina et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…[17] epi-Inositol 7: Shaldubina and co-workers showed that epi-inositol, another ''non-natural'' isomer, has the ability to modify the expression of the yeast INO1 gene encoding the myo-inositol-3-phosphate synthase. [18] epi-Inositol is thus biologically active in its ability to affect the regulation of the myo-inositol biosynthetic pathway. myo-Inositol phosphates, especially myo-inositol 1,4,5-trisphosphate [myo-Ins(1,4,5)P 3 ], act as intracellular second messengers.…”
Section: Neo-inositolmentioning
confidence: 99%
“…[182] Lithium is a classical inhibitor of the phosphoinositide In yeast epi-inositol has no effect on inositol monophosphatase but does inhibit the expression of the INO1 gene (encoding inositol-1-phosphate synthase) resulting in lower conversion of glucose-6-phosphate to D-myo-inositol 3-phosphate than might otherwise be the case. [184] epi-Inositol thus reverses the lithium-induced increase in INO1 expression. The daily intraperitoneal injection of epi-inositol into rats reduced anxiety levels compared to controls and was more effective than myo-inositol.…”
Section: Biology and Medicinementioning
confidence: 88%